Can we determine whether physical limitations are more prevalent in the US than in countries with comparable life expectancy? - Dana A. Glei; Noreen Goldman; Carol D. Ryff; Maxine Weinstein (Elsevier, 2017)
We evaluate the variability in estimates of self-reported physical limitations by age across four nationally representative surveys in the US. We consider its implications for determining whether, as previous literature suggests, the US estimates reveal limitations at an earlier age than in three countries with similar life expectancy: England, Taiwan, and Costa Rica. Based on cross-sectional data from seven population-based surveys, we use local mean smoothing to plot self-reported limitations by age for each of four physical tasks for each survey, stratified by sex. We find substantial variation in the estimates in the US across four nationally-representative surveys. For example, one US survey suggests that American women experience a walking limitation 15 years earlier than their Costa Rican counterparts, while another US survey implies that Americans have a 4-year advantage. Differences in mode of survey may account for higher prevalence of limitations in the one survey that used a self-administered mail-in questionnaire than in the other surveys that used in-person or telephone interviews. Yet, even among US surveys that used the same mode, there is still so much variability in estimates that we cannot conclude whether Americans have better or worse function than their counterparts in the other countries. Seemingly minor differences in question wording and response categories may account for the remaining inconsistency. If minor differences in question wording can result in such extensive variation in the estimates within a given population, then lack of comparability is likely to be an even greater problem when examining results across countries that do not share the same language or culture. Despite the potential utility of self-reported physical function within a survey sample, our findings imply that absolute estimates of population-level prevalence of self-reported physical limitations are unlikely to be strictly comparable across countries-or even across surveys within the same population.